Pemikiran Politik Islam : Studi Pemikiran Al-Mawardi dan Relevansinya di Indonesia - Ayuni Anggun Pratiwi; Hilma Kamila; Nafisatun Nikmah; Lina Marlina (Journal of Islamic Economics and Finance, 2025)
This article delves into the political thought of Al-Mawardi and its relevance to the contemporary political landscape of Indonesia. As a classical Islamic thinker, Al-Mawardi emphasized the necessity of a strong and stable government based on Sharia principles. His ideas on leadership, state authority, and the relationship between scholars and rulers remain fundamental in Islamic political studies. Using a qualitative approach and a descriptive-analytical method, this study explores how Al-Mawardi’s concepts continue to be applicable in modern Indonesian politics. The findings reveal that several of his ideas, such as the concept of ideal leadership and the role of the government in maintaining stability, remain relevant within Indonesia’s political system. This is particularly evident in efforts to establish a just government that prioritizes public welfare while aligning with Islamic values.